Pengaruh Media Poster Empat Kata Ajaib terhadap Interaksi Sosial Siswa di SDN 1 Lendang Kunyit - Ayuditiya Prihatin; Darmiany; Radiusman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of the four magic words poster media on students' social interactions at SDN 1 Lendang Kunyit. This study uses a quantitative research method of the Pre-Experimental Design type. Pre-Experimental Design is an experimental research design that does not have a control class or adequate control over external variables.  The research design used was a One-Group Pretest-Posttest. This design involved only one group. The group was first given a pretest, followed by treatment using learning media in the form of posters displaying the four magic words. Finally, the group was given a posttest. The sample in this study was determined by the Purposive Sampling technique. The sample in this study was all students of grades IV and V of SDN 1 Lendang Kunyit with a total of 30 students. The data collection process was carried out through questionnaires and observations, then the data obtained were analyzed using the Paired Sample T Test. The results of the analysis showed that the t-count value was greater than the t-table (7.387 > 2.045) and the significance value (p-value) <0.001 was smaller than 0.05. Thus, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. This means that the four magic words poster media had an effect on students' social interactions at SDN 1 Lendang Kunyit. This was also evidenced by an increase in the average score from 76.63 in the pretest to 88.23 in the posttest, indicating an improvement in students' social interactions. All indicators of social interaction, including conversation, cooperation, empathy, and mutual understanding, improved after being given the Four Magic Words poster.